Vulnerability Assessment of Lifestyle and Livelihoods in a High Risk Erosion Area of India by Using Time Use Micro Data in Two Coastal Fishing Communities - Iwasaki, Shimpei (International Journal of Asian Social Science, 2018)
Coastal erosion is a universal problem. Coastal landforms are highly dynamic and modified by natural and man-made processes. To handle coastal erosion, many researchers put much greater emphasis on the assessment of spatial and temporal changes of shoreline using satellite data, but not much attention was focused on the socio-economic condition of those who live in the high risk eroded area. With this recognition, this article explores vulnerability assessment of lifestyle and livelihoods in the high risk eroded area of Odisha state of India, by comparing two coastal fishing communities (high risk eroded area and non-high risk one) and by applying time use approach to collect comprehensive information on human activities. The findings revealed that there were several major differences between the two communities in the time spent on paid work, unpaid work, and social, cultural, and recreational work. Easy access to the ocean was one of the influence factors determining their settlement in the high-risk one while the psychological response to reduce the fear of natural hazards was found. Besides, the wasting time and spending for house maintenance might influence their livelihood assets and reduce development setbacks related to an unprecedented crisis. The lessons learned from the case study imply that the time use research is used to investigate the vulnerability of natural hazards while identifying coping strategies to mitigate disaster risk in high risk erode area, and enhance livelihoods.